2021
DOI: 10.1038/s41598-021-90881-5
|View full text |Cite
|
Sign up to set email alerts
|

The intestinal microbiota contributes to the growth and physiological state of muscle tissue in piglets

Abstract: Although the importance of the intestinal microbiota in host growth and health is well known, the relationship between microbiota colonization and muscle development is unclear. In this study, the direct causal effects of the colonization of gut microorganisms on the muscle tissue of piglets were investigated. The body weight and lean mass of germ-free (GF) piglets were approximately 40% lower than those of normal piglets. The deletion of the intestinal microbiota led to weakened muscle function and a reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 73 publications
1
36
0
Order By: Relevance
“…Wildlife is more vulnerable to the threat of diarrhea due to the lack of timely, effective veterinary intervention. Studies have confirmed that the gut microbiome plays an important role in host growth, development, and immune response (35,36). Changes in the gut microbial community not only lead to gastrointestinal diseases, such as metabolic syndrome, obesity, and diarrhea (37,38), but also cause diseases outside the digestive system, including central nervous system disorders (39), cardiovascular disease (40), etc.…”
Section: Discussionmentioning
confidence: 98%
“…Wildlife is more vulnerable to the threat of diarrhea due to the lack of timely, effective veterinary intervention. Studies have confirmed that the gut microbiome plays an important role in host growth, development, and immune response (35,36). Changes in the gut microbial community not only lead to gastrointestinal diseases, such as metabolic syndrome, obesity, and diarrhea (37,38), but also cause diseases outside the digestive system, including central nervous system disorders (39), cardiovascular disease (40), etc.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to the heart, autophagy might be regulated by the gut microbiota in other muscles. Recently, high-throughput RNA-seq analysis revealed that the expression levels of autophagy-related genes ( LC3A , LC3B , and Beclin-1 ) were modulated in the skeletal muscles of germ-free piglets compared to control piglets[ 79 ]. Moreover, germ-free piglets harbored decreased expression of mTOR and AKT and their phosphorylated forms, phospho-mTOR (S2448) and phospho-AKT (S473), respectively, compared to control piglets[ 79 ].…”
Section: Systemic Effects Of the Gut Microbiota On Host Autophagymentioning
confidence: 99%
“…Recently, high-throughput RNA-seq analysis revealed that the expression levels of autophagy-related genes ( LC3A , LC3B , and Beclin-1 ) were modulated in the skeletal muscles of germ-free piglets compared to control piglets[ 79 ]. Moreover, germ-free piglets harbored decreased expression of mTOR and AKT and their phosphorylated forms, phospho-mTOR (S2448) and phospho-AKT (S473), respectively, compared to control piglets[ 79 ]. FMT of germ-free piglets with stools collected on healthy donors pigs was effective in restoring the amounts of phospho-AKT and mTOR to a level similar to that of controls[ 79 ].…”
Section: Systemic Effects Of the Gut Microbiota On Host Autophagymentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies concerning meat quality have shown that muscle glycogen utilization, protein denaturation, degradation of muscle, and muscle fiber diameter and density affected the pH, water-holding capacity, and shearing force of meat ( 13 15 ). Additional studies concerning the gut microbiota-muscle axis showed that gut microbiota contributed to growth and the physiological state of muscle tissue ( 16 ), the substance and energy metabolism of muscle ( 17 ), as well as the synthesis and function of skeletal muscle ( 18 ). Therefore, the intestinal microbiota could be strategically regulated to improve meat quality through the muscle-gut microbiota axis.…”
Section: Introductionmentioning
confidence: 99%